Fine‐tuned regulation of the K+/H+ antiporter KEA3 is required to optimize photosynthesis during induction. (3rd February 2017) - Wang, Caijuan; Yamamoto, Hiroshi; Narumiya, Fumika; Munekage, Yuri Nakajima; Finazzi, Giovanni; Szabo, Ildiko; Shikanai, Toshiharu
Summary: KEA3 is a thylakoid membrane localized K + /H + antiporter that regulates photosynthesis by modulating two components of proton motive force (pmf), the proton gradient (∆pH) and the electric potential (∆ψ). We identified a mutant allele of KEA3, disturbed proton gradient regulation ( dpgr ) based on its reduced non‐photochemical quenching (NPQ) in artificial (CO2 ‐free with low O2 ) air. This phenotype was enhanced in the mutant backgrounds of PSI cyclic electron transport ( pgr5 and crr2‐1 ). In ambient air, reduced NPQ was observed during induction of photosynthesis in dpgr, the phenotype that was enhanced after overnight dark adaptation. In contrast, the knockout allele of kea3‐1 exhibited a high‐NPQ phenotype during steady state in ambient air. Consistent with this kea3‐1 phenotype in ambient air, the membrane topology of KEA3 indicated a proton efflux from the thylakoid lumen to the stroma. The dpgr heterozygotes showed a semidominant and dominant phenotype in artificial and ambient air, respectively. In dpgr, the protein level of KEA3 was unaffected but the downregulation of its activity was probably disturbed. Our findings suggest that fine regulation of KEA3 activity is necessary for optimizing photosynthesis. Significance Statement: A thylakoid membrane‐localized K + /H + antiporter (KEA3) regulates photosynthesis by modulating the proton gradient (∆pH) and the electric potential (∆ψ). Here, by characterizing a point mutant allele of KEA3 and a knockout allele, we suggest that fine regulation of KEA3 activity is necessary for optimizing photosynthesis in fluctuating light conditions.